Signed Languages in Education in Europe - a preliminary exploration - LEESON, LORRAINE (Council of Europe, 2006)
This paper briefly describes some issues concerning education in signed languages insofar as the availability of data permits at this time. In order to contextualise the discussion, we briefly outline the diversity of approaches that are applied in a European context (oralism/auralism, `Total-communication?, bilingualism) and make reference to the specific issues that arise for deaf/ hard of hearing children who do not attend a special school/ unit for the deaf in terms of accessing a signed language. We will briefly discuss the implications for school learning by deaf and hearing impaired students of whatever approaches are adopted to signed language and to the national language(s). We then turn to discuss the teaching of signed languages as a subject in the curriculum (LS), and will also highlight where non-indigenous signed languages are taught as `foreign languages?. We will refer to the teaching of foreign languages to Deaf / hard of hearing children (where data is available). We will also outline the issue of how signed languages are taught across the curriculum (LAC) ? as a medium of instruction for other school subjects.
PUBLISHED
Keywords: signed languages; education for the deaf